Factors Affecting The Smallholder Sugarcane Plantation Area - Eka Miftakhul Jannah; Aditya Arief Rachmadhan; Meidaliyantisyah Meidaliyantisyah; Jekvy Hendra (Jurnal Penelitian Pertanian Terapan, 2022)
The decrease of the smallholder sugarcane area is the major problem for the Indonesian plantation white sugar industry. This study aims to analyze factors that affecting the decrease of the smallholder sugarcane area. This study uses a panel data econometric model; using cross-sectional data from five provinces of smallholder sugarcane base area (East Java, Central Java, Lampung, West Java, and Yogyakarta) with monthly time series from 2014 to 2018. Estimates use the generalized least square (GLS) method. The results showed that the decrease of the smallholder sugarcane area was significantly affected by: (1) the decrease of sugar factories that were actively operating, (2) the increase of labor wages in the estate crops sector, (3) land competition with corn commodities, and (4) the increase of residential areas due to growth of population. The opening of new sugar factories out of Java Island is an alternative to encourages land clearing for smallholder sugarcane areas.